Effects of the COVID-19 related economic downturn on greenhouse gas emissions in Austria - Franz Sinabell; Mark Sommer; Gerhard Streicher (Austrian Institute of Economic Research (WIFO), 2020)
The measures taken to limit the spread of the COVID-19 virus, which at the same time severely restrict economic activity in many countries, have consequences not only on unemployment, trade, production, income and value added, but also on the environment. This analysis examines the effects on greenhouse gas emissions in Austria. For this purpose, a new, lean and very flexible model, ALICE, was developed, which quantifies the short to medium-term effects of changes in production and consumption with regard to output, value added and greenhouse gas emissions. In order to determine the consequences as precisely as possible, 74 economic activities and households are distinguished. The model results show not only the direct consequences, but also the consequences resulting from the interdependence of the economic system. The scenario presented here is based on the forecast published by WIFO in late June 2020, which forecasts a decline in gross domestic product by 7 percent in 2020. The sector-specific declines in value added and expected changes in household consumption behaviour are the input parameters for the model that calculates the associated greenhouse gas emissions. Greenhouse gas emission - as defined by the Austrian inventory - is estimated to decline by 9.9 percent. This decline is due to the change of economic activities. Factors that also affect the level of emissions, such as ambient temperatures, changes in land use and forest growth, are not considered here. Following the conventions of the greenhouse gas inventory, international aviation is not included in the calculation either. There are several uncertainties because the economy may suffer even more than expected in June 2020. The actual production of industries and the behaviour of households throughout the year, especially with regard to their travel activities, may unfold in a different manner than expected.
Keywords: G12; Q01; Q54; 330; TP_COVID